PRODUCT PACKAGING DESIGN TRAINING USING SMARTPHONE APPLICATIONS TO INCREASE THE SALES VALUE OF MSME PRODUCTS - Rivaldo Branco Guterres (Universitas Nias Raya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in national economic development; however, many MSME actors struggle to compete due to poor product packaging quality. This community service program aimed to enhance the packaging design capabilities of MSME actors through structured training using smartphone applications. A total of 25 MSME participants from diverse product sectors completed a two-day, practice-based training program covering design principles, smartphone application usage, and regulatory labeling requirements. Pre- and post-training assessments, facilitator observations, and focus group discussions were employed to evaluate program outcomes. Results indicated that 84% of participant designs achieved market-ready or near-market-ready quality, with average knowledge scores improving by 67% and self-efficacy scores increasing by 74% relative to pre-training baselines. Participants reported strong intentions to continue using design applications independently and expressed confidence in the commercial potential of their redesigned packaging. The findings demonstrate that smartphone-based packaging design training is an effective, accessible, and cost-efficient approach to improving MSME product competitiveness and increasing sales value, with significant implications for digital empowerment and creative economy development.